Effect of seed priming on the germination of upland rice (Oryza sativa L.) sown in acidic soil - AGUSTIANSYAH, AGUSTIANSYAH; TIMOTIWU, PAUL BENYAMIN; ADHINUGRAHA, QUDUS SABHA (Universitas Syiah Kuala, 2025)
Upland rice is a type of rice that can be grown in Ultisol. The obstacles to cultivating plants in Ultisol are low pH and high aluminum content which hinders seed germination. Seed priming is a technology that can overcome problems with Ultisol. The aim of this research was to determine the effect of priming on the germination of upland rice seeds in acid soil conditions. The experiment conducted on non-factorial Completely Randomized Design (CRD) consisting of 8 treatments with 3 replications. The data were analyzed for variance and followed by Honest Significant Differences (HSD) at 5% using the Statistic R Program. Seed priming treatments tested were (1) Untreatment; (2) Hydropriming; (3) priming GA3 25 ppm; (4) priming GA3 50 ppm; (5) priming PEG 6000 10%; (6) priming PEG 6000 20%; (7) 0.5% KNO3 priming, and (8) 1% KNO3 priming. Rice seed are soaked in priming for 24 hours. The upland rice seeds of the Inpago 13 Fortiz variety were planted in Ultisol soil media with a pH of 4.45, Al content of 0.44%, and Fe 1.37%. The results showed that the priming treatment increased the germination and themost effective treatment was priming GA3 50 ppm, each value of showed germination (92.38%), germination speed (19.71% day-1), vigor index (83.81%), and time of appearance of plumule (2.96 day).